A polymorphic Y chromosome microsatellite locus in cattle - Hanotte, Olivier H.; Okomo, M.; Verjee, Y.; Rege, J.E.O.; Teale, A.J. (1997)
DNA samples from 30 Friesian, 18 N'Dama, 30 Sahiwal and 18 Barotse (derived from Bos taurus and B. indicus) cattle were amplified by the polymerase chain reaction using previously described primer sequences for amplification of the Y chromosome locus INRA124. A polymorphism with 2 alleles was detected; Friesians and N;Dama had only the 132-bp allele, the Sahiwal had only the 130-bp allele and the Barotses had both.